The Outcomes of Lactoferrin as New Treatment of Iron Deficiency Anaemia in Patients on Regular Haemodialysis: A Systematic Review - Ogek Dwi Shavitri; I Made Bakta (Green Publisher Indonesia, 2026)
Iron deficiency anaemia (IDA) is a common and significant complication among patients with chronic kidney disease (CKD), particularly those undergoing regular haemodialysis. Conventional iron supplementation, although widely used, is often limited by gastrointestinal side effects, inflammation, and suboptimal iron utilization. Therefore, alternative therapies such as lactoferrin, an iron-binding glycoprotein with anti-inflammatory and immunomodulatory properties, have gained increasing attention. This study aims to evaluate the effectiveness and safety of lactoferrin as a treatment for IDA in CKD patients on regular haemodialysis. This research employed a systematic review design following PRISMA 2020 guidelines. A comprehensive literature search was conducted across major databases, including PubMed, Scopus, Google Scholar, ScienceDirect, and ProQuest. Eligible studies included randomized controlled trials, interventional, and observational studies involving adult CKD patients receiving lactoferrin therapy. Data were analyzed narratively to compare haematological and inflammatory outcomes. The findings indicate that lactoferrin significantly improves haemoglobin levels, serum iron, and transferrin saturation, while reducing inflammatory markers such as hepcidin, C-reactive protein, and interleukin-6. Compared to conventional iron therapy, lactoferrin demonstrates better tolerability and fewer adverse effects. In combination with erythropoiesis-stimulating agents, it provides comparable hematologic outcomes with additional anti-inflammatory benefits. In conclusion, lactoferrin is a promising and well-tolerated adjunct therapy for managing IDA in CKD patients undergoing haemodialysis. However, further large-scale studies are needed to confirm its long-term efficacy and optimal clinical application.